Synthesis, Applications and Biological Impact of Nanocellulose - Sunasee, Rajesh; Ckless, Karina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book aims to highlight recent advances in the synthesis of nanocellulose and surface modifications for the design of functional nanocellulose, as well as its applications and potential biological impact. It features two review articles and four original research articles which targets a broad readership of chemists, materials scientists, biochemists, nanotechnologists and others with an interest in nanocellulose research.